The Effect of the Educational Psychology Approach on the Learning Motivation of Islamic Religious Education in Students - Siti Aisyah; Setia Budiyanti (Jurnal Edusci, 2026)
Background. The application of psychological principles in Islamic religious education is very important for students to develop optimally. The role of educational psychology to improve the quality of the educational process in a certain unit. In other words, the role of educational psychology can increase student competitiveness. Purpose. To know the psychological perspective in Islamic religious education on campus. Method. This study employs a literature review approach, systematically gathering and critically examining data and findings reported across a range of prior research. Results. Islamic psychology plays a substantial role in children's education, and its connection to Islamic educational principles is notably strong. Conclusion. The application of educational psychology in Islamic religious learning is by strengthening and punishment. Reinforcement, for example, by giving praise, grades or prizes to students as an appreciation for their achievements. Meanwhile, punishment is applied in the learning of Islam.